Wrist Arthroscopy: Positioning, Portal Placement, and Diagnostic Evaluation - Julia A.V. Nuelle, M.D.; Bradley J. Vivace, M.D.; Abdulai Bangura, M.D.; Clayton W. Nuelle, M.D. (Arthroscopy Techniques)
Wrist arthroscopy can be an invaluable technique with both diagnostic and therapeutic utility for surgeons treating pathologies of the wrist. Its use has increased in recent years for a myriad of diagnoses. Understanding the foundations of the preparation for and performance of diagnostic arthroscopy is critical to the successful execution of arthroscopic treatment of pathologies of the wrist. This Technical Note aims to describe a reproducible surgical technique for wrist arthroscopy, including patient positioning, portal placements, and diagnostic evaluation.